STUDI KRITIS TERHADAP SARANA IBADAH - Kholid Saifulloh (Al-Majaalis : Jurnal Dirasat Islamiyah, 2019)
Each goal has a means that helps to get to that goal. Likewise worship which is the main purpose of human creation, Allah subhahu wa ta'a he said: "and I did not create jinn and humans except to worship Me"2 . However, something that became a means for worship varied, as did the law of the facility. Therefore, the author tries to divide it based on the four classifications the authors describe in this paper. Furthermore, the authors conclude that the law of worship facilities is inseparable from the four laws: mubah, haram, sunna, and obligatory.